Stacking Faults in the single crystals - Mihir M. Vora; Aditya M. Vora (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The single crystals of InxMoSe₂ (0 ≤ x ≤ 1) and Re-doped MoSe₂ viz. MoRe₀.₀₅Se₁.₉₉₅, MoRe₀.₀₀₁Se₁.₉₉₉ and Mo₀.₉₉₅Re₀.₀₀₅Se₂ have been grown by a direct vapour transport technique (DVT) in the laboratory. Structural characterization of these crystals was made using the XRD method. The particle size for a number of reflections has been calculated using the Scherrer formula. There are considerable variations appearing in deformation (α) and growth (β) fault probabilities in InxMoSe₂ (0 ≤ x ≤ 1) and Re-doped MoSe₂ single crystals due to their off-stoichiometry, which possesses the stacking fault in the single crystal.